Development and Validation of RP-HPLC Method for the Simultaneous Estimation of Methionine, Pyridoxine Hydrochloride and Nicotinamide in Combined Dosage Form - Saini, Shipra; Mandal, Sulekha; Agarwal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2021)
Analytical chemistry is one of the important branches of science which deals with the study of separation, identification and quantification of various natural and chemical compounds. Quantitative analysis is having supremacy from the point of pharmaceutical chemistry. Quantification methods include chromatographic techniques, spectrophotometery, fluorimetery etc. One of the accurate method for quantitative analysis is High Performance Liquid Chromatography (HPLC). In the present manuscript, a reverse phase – HPLC method was developed for the simultaneous determination of Methionine, Pyridoxine hydrochloride and Nicotinamide in combined dosage form and validation of the developed method. The development of method includes selection of mobile phase, chromatographic method and wavelength whereas validation involves the parameters like linearity, accuracy, precision, Limit of detection (LOD), Limit of Quantification (LOQ), robustness, system suitability of the developed method. The result showed that the developed method is best suited to the simultaneous determination of Methionine, Pyridoxine hydrochloride and Nicotinamide and validated as per standards.